A HISTORICAL AND JURIDICAL REVIEW OF THE DEVELOPMENT OF ISLAMIC EDUCATION WITHIN THE NATIONAL EDUCATION SYSTEM IN INDONESIA - Khasanah, Farida Nurul; Yusuf, Moh.; Fidiya, Nadira Putri; Adibah, Ida Zahara; Kahfi, Nazih Sadatul (FAJAR Jurnal Pendidikan Islam, 2025)
The urgency of integrating Islamic education in Indonesia's national education system is becoming increasingly important amid the challenges of globalisation, digital transformation, and the need to strengthen the nation's cultural identity. This article aims to examine the development of Islamic education in Indonesia through historical and juridical approaches and examine its contemporary dynamics. The method used is qualitative research based on library research with a descriptive-analytical approach. Data sources were obtained from the latest relevant academic literature, analysed through thematic review techniques. The results of the study show that Islamic education has strong historical roots, is juridically recognised, but faces implementative challenges and the need for innovation in curriculum and learning technology. This article contributes to the strengthening of educational integration theory and offers a new perspective in designing educational policies that are inclusive and responsive to the times. Future research is expected to be able to examine the practice of Islamic education integration empirically in various local contexts.